Proliferation of Private Food Safety Standards in Indian Seafood Export Supply Chain – A Study on Kerala - Raymond, Asha; A. V. Shibu (Fishery Technology, 2023)
The private standards play an important role in food safety governance and determining market access in international trade. In recent years there has been an increase in seafood certification and consumer labels in the European retail market. The seafood processors in Kerala who have the key responsibility of ensuring food quality and safety are increasingly adopting these standards. About 45 percent of the seafood processing companies in Kerala have implemented private/voluntary food safety standards such as International Organization for Standardization (ISO) 22000, British Retail Consortium (BRC), Food Safety System Certification (FSSC) 22000, Best Aquaculture Practices (BAP), and International Featured Standard (IFS). Despite the Global Food Safety Initiative (GFSI) benchmarking and harmonization of these standards, nearly 20 % of seafood exporting companies have implemented multiple food safety management systems (MFSMS) in Kerala which substantiates the inadequacy of the purpose of GFSI benchmarked standards. Hence there is a need to develop a national food quality and safety standard that can be harmonized with the private standards proliferating in the market so that the advantages can be utilized by producers and processors of all food types and food businesses in India.